Pamiparib in combination with tislelizumab in patients with advanced solid tumours: results from the dose-escalation stage of a multicentre, open-label, phase 1a/b trial. Issue 9 (September 2019) - Friedlander, Michael; Meniawy, Tarek; Markman, Ben; Mileshkin, Linda; Harnett, Paul; Millward, Michael; Lundy, Joanne; Freimund, Alison; Norris, Christie; Mu, Song; Wu, John; Paton, Virginia; et al.
Summary: Background: Rationale exists for combined treatment with immune checkpoint inhibitors and poly (ADP-ribose) polymerase (PARP) inhibitors in a variety of solid tumours. This study aimed to investigate the safety and antitumour effects of pamiparib, an oral PARP 1/2 inhibitor, combined with tislelizumab, a humanised anti-PD-1 monoclonal antibody, in patients with advanced solid tumours and to determine the optimum doses for further evaluation. Methods: We did a multicentre, open-label, phase 1a/b study at five academic sites or community oncology centres in Australia. We recruited adults (aged ≥18 years) with advanced solid tumours who had received one or more previous lines of therapy, with an Eastern Cooperative Oncology Group performance score of 1 or less, and a life expectancy of 12 weeks or more. Patients were enrolled into one of five dose-escalation cohorts, with dose-escalation done in a 3 + 3 design. Cohorts 1–3 received intravenous tislelizumab 2 mg/kg every 3 weeks plus 20, 40, or 60 mg oral pamiparib twice daily, respectively; cohorts 4 and 5 received 200 mg intravenous tislelizumab every 3 weeks plus 40 or 60 mg oral pamiparib twice daily, respectively. The primary endpoints of the phase 1a dose-escalation part of the study were safety and tolerability, including the occurrence of dose-limiting toxicities and determination of the maximum tolerated dose and recommended phase 2 dose. All primary endpoints were analysed in the safety analysis set, which included all patients who received at least one dose of tislelizumab or pamiparib, with the exception of the occurrence of dose-limiting toxicities, which was analysed in the dose-limiting toxicity analysis set, which included all patients who received at least 90% of the first scheduled tislelizumab dose and at least 75% of scheduled pamiparib doses, or who had a dose-limiting toxicity event during cycle 1. Reported here are results of the phase 1a dose-escalation stage of the trial. This trial is registered with ClinicalTrials.gov, number NCT02660034, and is ongoing. Findings: Between Jan 22, 2016, and May 16, 2017, we enrolled 49 patients (median age 63 years [IQR 55–67]), all of whom received at least one dose of pamiparib or tiselzumab. Four patients had dose-limiting toxicities (intractable grade 2 nausea [n=1] and grade 3 rash [n=1] in cohort 4, and grade 2 nausea and vomiting [n=1] and grade 4 immune-mediated hepatitis [n=1] in cohort 5). The recommended phase 2 dose was tislelizumab 200 mg every 3 weeks plus pamiparib 40 mg twice daily (the dose given in cohort 4). The most common treatment-emergent adverse events were nausea (in 31 [63%] of 49 patients), fatigue (26 [53%]), diarrhoea (17 [35%]), and vomiting (15 [31%]). 23 (47%) of 49 patients had immune-related adverse events, of whom nine (39%) had asymptomatic grade 3–4 hepatic immune-related adverse events, which were reversible with corticosteroid treatment. The most common adverse event of grade 3 or worse severity was anaemia (in six [12%] patients) and no grade 5 adverse events were reported. Hepatitis or autoimmune hepatitis was the only serious adverse event to occur in two or more patients (in four [8%] patients). At a median follow-up of 8·3 months (IQR 4·8–12·8), ten (20%) of 49 patients achieved an objective response according to Response Evaluation Criteria in Solid Tumours (RECIST) version 1.1, including two complete responses and eight partial responses. Interpretation: Pamiparib with tislelizumab was generally well tolerated and associated with antitumour responses and clinical benefit in patients with advanced solid tumours supporting further investigation of the combination of pamiparib with tislelizumab. Funding: BeiGene.